CAPITAL STRUCTURE MODEL (Empirical Study on IDX 2020-2022) - Candrika Dewi; Riswan Riswan; Khairudin Khairudin (Transpublika Publisher, 2024)
The food and beverage industry are constantly evolving and shaped by consumer preferences, making it crucial for companies to consider the various factors that impact their revenue streams. Analyzing the structure of a company's assets and the rate of its sales growth are crucial factors to consider, as they greatly influence the financial management practices of the company. Asset structure means what a company owns, and sales growth shows if the company is making more or less money. The aim of this research is to examine how the capital structure is influenced by asset structure, sales growth, and the role of profitability in mediating this connection. The study utilized a quantitative research methodology. The research population consisted of companies in the food and beverage subsector on the IDX from 2020 to 2022. A total of 23 companies were selected as the sample over a 3-year period, resulting in 69 data points using purposive sampling technique. The data analysis involved multiple linear regression analysis with the assistance of SPSS version 17. The study's results show that both the composition of assets and the growth in sales have a favorable and noteworthy influence on the structure of capital. Additionally, profitability plays a role in connecting the asset structure with the capital structure, as well as linking sales growth with the capital structure.